ASSOCIATION BETWEEN PHYSICAL ACTIVITY AND SOCIODEMOGRAPHIC FACTORS WITH OBESITY AMONG ADULTS IN JAKARTA: ANALYSIS OF THE 2023 INDONESIAN HEALTH SURVEY - Arum Puspitasari; Resti Yulianti Sutrisno; Helda Helda; Sofwatul Hanim (Jurnal Kesehatan Kusuma Husada, 2026)
Background: Obesity is a global public health problem that carries an elevated risk of noncommunicable diseases. Behavioral factors that may be modifiable should be assessed to design effective preventive programs. This study aimed to determine the association of physical activity, sociodemographic factors, and obesity among adults in Jakarta.Methods: This study employed a quantitative, analytical, cross-sectional design. Data collected by the second wave of the 2023 Indonesian Health Survey. We analyzed 7.163 adult participants. Statistical analyses used chi-square and survey-adjusted logistic regression, and risk was measured as Prevalence Ratios (PR) with 95% Confidence Intervals (CI).Results: The prevalence of obesity in this study was 49.67%. Logistic regression analysis showed a significant relationship between obesity and physical activity (p=0.045; PR=1.126), age 30-44 years (p=0.000; PR=2.213), age 45-59 years (p=0.000; OR=2.352), gender (p=0.000; OR=1.713), employment status (p=0.000; OR=1.653), and marital status (p=0.000; OR=2.437). Conversely, educational level did not show a statistically significant relationship with obesity (p>0.05). Moreover, levels of physical activity, marital status, sex, and employment status accounted for the factors that increased the likelihood of adult obesity. Conclusion: Adult obesity in Jakarta is significantly associated with sex, age, sex, physical activity level, employment status, and marital status. These findings indicate the need to address targeted behavior changes, especially increasing levels of physical activity and exercise to encourage cognitive dissonance of increasing the likelihood of obesity through healthy weight and obese adults, particularly in middle-aged and women.